2004
DOI: 10.1194/jlr.m300509-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Decreased membrane fluidity and altered susceptibility to peroxidation and lipid composition in overweight and obese female erythrocytes

Abstract: The increased generation of reactive oxygen species that occurs in the condition of obesity may be responsible for oxidative injury to erythrocyte membranes, which could lead to a decrease in tissue oxygenation. Therefore, we have looked into the effects of obesity on both indexes of oxidative damage and physical-chemical properties of erythrocyte membranes in 50 overweight or obese [25 Ͻ body mass index (BMI) Ͻ 33], normotensive, nondiabetic women and 50 age-matched lean healthy women (BMI Ͻ 25). In the obese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
113
4
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(132 citation statements)
references
References 22 publications
11
113
4
4
Order By: Relevance
“…[29][30][31][32] It has also been shown that there is an obesity-related decrease in glutathione content of the erythrocytes. 7,8 In addition, Yoshida et al 33 reported that, in diabetes mellitus often accompanying obesity, GSH synthesis and conjugate transport are impaired in erythrocytes. However, this is the first study concerning the effects of obesity on the glutathione S-conjugate transport.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[29][30][31][32] It has also been shown that there is an obesity-related decrease in glutathione content of the erythrocytes. 7,8 In addition, Yoshida et al 33 reported that, in diabetes mellitus often accompanying obesity, GSH synthesis and conjugate transport are impaired in erythrocytes. However, this is the first study concerning the effects of obesity on the glutathione S-conjugate transport.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 On the other hand, several investigators have shown that the levels of lipid peroxidation products were elevated in various tissues including blood in obesity. [36][37][38][39] It has been previously reported that transport systems for glutathione S-conjugates play significant roles in the biotransformation of toxic products arising from oxidative stress-induced lipid peroxidation, as well as various GSH S-conjugate with/which has mutagenic and carcinogenic activities. 16,17 Thus, it is of interest to see how glutathione conjugate transport in cells of obese can protect cells from CDNB-induced oxidative damage by exporting DNP-SG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Obesity is a risk factor for OSA, 38 and obesity has been associated with reduced RBC omega-3 status. 39 The latter relations are postulated to be secondary to increased peroxidation of RBC membrane FAs. It is thus possible that increased membrane FA oxidative damage could be a common thread tying together low omega-3 FA status, OSA, obesity, and CVD.…”
Section: Dha (% Of Total Fatty Acids) Female Malementioning
confidence: 99%